2016
DOI: 10.1016/j.jad.2016.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Risk of incident cardiovascular events amongst individuals with anxiety and depression: A prospective cohort study in the east London primary care database

Abstract: Patients with depression have increased risk of cardiovascular events. The finding of no increased cardiovascular risk in those with anxiety after adjusting for cardiovascular risk factors is of clinical importance and highlights that the adequate control of traditional risk factors is the cornerstone of cardiovascular disease prevention. Targeting management of classical cardiovascular risk factors and evaluating the risks of antidepressant prescribing should be prioritized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
1
17
0
3
Order By: Relevance
“…(27) The identification of patients with anxiety disorders was conducted in two studies, (26,27) with DSM III, DSM IV, and ICD-9 criteria,(31-33) another five studies used scales, (23-25, 28, 30) and diagnoses recorded in primary care notes were used in another study. (29) The follow up time ranged from ten to 22 years and the proportion of incidents strokes observed ranged from 0.2 to 12.6% with larger proportions of strokes observed in studies with longer follow up. (28,30) Three studies excluded patients with past medical history of stroke, (25,28,29) two excluded patients with history of stroke in the year before study entry, (26,27) and one excluded those with past medical history of cardiovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…(27) The identification of patients with anxiety disorders was conducted in two studies, (26,27) with DSM III, DSM IV, and ICD-9 criteria,(31-33) another five studies used scales, (23-25, 28, 30) and diagnoses recorded in primary care notes were used in another study. (29) The follow up time ranged from ten to 22 years and the proportion of incidents strokes observed ranged from 0.2 to 12.6% with larger proportions of strokes observed in studies with longer follow up. (28,30) Three studies excluded patients with past medical history of stroke, (25,28,29) two excluded patients with history of stroke in the year before study entry, (26,27) and one excluded those with past medical history of cardiovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…[12] A number of studies have demonstrated that a considerable percentage of patients with AMI experiences depressive symptoms,[34] which has an adverse impact on the cardiovascular prognosis. [5] However, little is known about how depressive symptoms contribute to cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that depression has negative effects on the course and consequences of CAD. Patients with depression have increased the risk of mortality following acute MI, unstable angina, and coronary artery bypass graft surgery . A study demonstrated that the risk of a major cardiac event within 12 months following a diagnosis of CAD was increased 2‐fold in patients with depression compared to those without depression .…”
Section: Discussionmentioning
confidence: 99%